AB0444 RISK FACTORS OF JOINT SURGERY IN RHEUMATOID ARTHRITIS TUNISIAN PATIENTS. (June 2019) - Saidane, Olfa; Gafsi, Leila; Barhoumi, Rim; Tekaya, Aicha Ben; Tekaya, Rawdha; Mahmoud, Ines; Abdelmoula, Leila
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory disease characterized by polyarticular synovial inflammation and progressive joint destruction. Orthopedic surgery is an integral part of the treatment of RA and it is mainly reserved for severe and advanced forms where there is a failure of medical treatment. Objectives: To assess the rate of joint surgery in rheumatoid arthritis (RA) Tunisian patients and to determine the risk factors of surgical treatment Methods: A retrospective cross sectional study over a period of 15 years including 500 Tunisian patients with RA was conducted. The prevalence of joint surgery indication has been evaluated. Clinical, paraclinical and therapeutic characteristics of RA were compared according to the need of surgical treatment Results: Mean age was 53.4 years. Female to male ratio was 5. The indication of joint surgery was noted in 59 patients (12%). Factors associated with joint surgery were delayed diagnosis (p = 0.037), long RA duration (p = 0.017), young onset of RA (p <0.001), presence of joint deformities (p = 0.034), presence of osteoporosis (p = 0.029), presence of antinuclear antibodies<0.001), combination therapy of methotrexate with other conventional synthetic disease-modifying anti-rheumatic drugs (csDMARDs) (p = 0.001), a short period of first medical treatment (p = 0.012) and high erythrocyte sedimentation rate (ESR) (p = 0.027). In multivariate analysis, three factors were independently related to the need of joint surgery: age at disease onset (OR 2.799 95%CI: 1.49-5.22 p=0.01), high ESR level (OR 2.807 95%CI: 1.5-5.24 p=0.01), and association of Methotrexate with other csDMARDs (OR 3.500 95%CI: 1.61-7.56 p=0.01) Conclusion: Twelve percent of RA patients needed joint surgery treatment. Predictive factors of surgical treatment were young age at disease onset, high ESR level and association of methotreaxte with other csDMARDs References: [1] Waljee J, Zhong L, Baser O, Yuce H, Fox DA, Chung KC. The incidence of upper and lower extremity surgery for rheumatoid arthritis among medicare beneficiaries. J Bone Joint Surg Am. 2015;97(5):403-10. [2] Kapetanovic MC, Lindqvist E, Saxne T, Eberhardt K. Orthopaedic surgery in patients with rheumatoid arthritis over 20 years: prevalence and predictive factors of large joint replacement. Ann Rheum Dis. 2008;67(10):1412-6. Disclosure of Interests: None declared